Cdk5-Dependent Mst3 Phosphorylation and Activity Regulate Neuronal Migration through RhoA Inhibition - Tang, Jing (J Neurosci, 2014)
The radial migration of newborn neurons is critical for the lamination of the cerebral cortex. Proper neuronal migration requires precise and rapid reorganization of the actin and microtubule cytoskeleton. However, the underlying signaling mechanisms controlling cytoskeletal reorganization are not well understood. Here, we show that Mst3, a serine/threonine kinase highly expressed in the developing mouse brain, is essential for radial neuronal migration and final neuronal positioning in the developing mouse neocortex. Mst3 silencing by in utero electroporation perturbed the multipolar-to-bipolar transition of migrating neurons and significantly retards radial migration. Although the kinase activity of Mst3 is essential for its functions in neuronal morphogenesis and migration, it is regulated via its phosphorylation at Ser79 by a serine/threonine kinase, cyclin-dependent kinase 5 (Cdk5). Our results show that Mst3 regulates neuronal migration through modulating the activity of RhoA, a Rho-GTPase critical for actin cytoskeletal reorganization. Mst3 phosphorylates RhoA at Ser26, thereby negatively regulating the GTPase activity of RhoA. Importantly, RhoA knockdown successfully rescues neuronal migration defect in Mst3-knockdown cortices. Our findings collectively suggest that Cdk5–Mst3 signaling regulates neuronal migration via RhoA-dependent actin dynamics.